PENINGKATAN LOYALITAS MUZAKKI DALAM MEMBAYAR ZAKAT MELALUI SERVICE EXCELLENCE - Yusuf Yusuf; La Ode Anto; Nofrivul Nofrivul (Imara: JURNAL RISET EKONOMI ISLAM, 2020)
This study aims to analyze the effect of service excellence on increasing Muzakki's loyalty in paying zakat at Baznas of Southeast Sulawesi Province. This research was conducted on the people of Southeast Sulawesi province who paid zakat at the Southeast Sulawesi Provincial Baznas of 120 people. Analysis of the data used in this study is multiple linear regression. The results of this study indicate that service excellence consisting of attitude, attention, action, ability, appereance, and accountability significantly plays a role in increasing Muzakki's loyalty